Governing science and technology under the international economic order: Regulatory divergence and convergence in the age of megaregionals by Shin-yi Peng, Han-Wei Liu and Ching-Fu Lin - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2021)
Trade and technology have a long history of interdependence. It was the trade along the ancient silk road that helped to spread the technologies of China – such as paper-making, gun power, compass, and moveable type printing – to Europe. These technologies helped to launch the Renaissance, the Reformation, and the Great Discoveries, which in turn set in motion globalization as we know today. As we enter the third decade of the twenty-first century, the role of science and technology grows even stronger in international trade. For example, the advancement of information and communications technology (ICT) has greatly facilitated the cross-border supply of services (and goods in some instances), which has become essential due to the pandemic that is raging around the world at the time of this writing. In view of these developments, the governance of science and technology under the international economic order becomes even more topical and timely today. By addressing these important governance issues, this book provides rich food for thought. The key question in any international economic order is about how to strike a balance between trade liberalization on the one hand, and regulatory autonomy on the other hand. This question has generated considerable and enduring challenges for WTO tribunals as they, in the application and interpretation of WTO rules, seek to achieve a balance between trade and non-trade values such as human life and health, the environment, public morals, consumers interests, and, increasingly, national security.